2011
DOI: 10.1165/rcmb.2009-0456oc
|View full text |Cite
|
Sign up to set email alerts
|

ST Depression, Arrhythmia, Vagal Dominance, and Reduced Cardiac Micro-RNA in Particulate-Exposed Rats

Abstract: Recently, investigators demonstrated associations between fine particulate matter (PM)-associated metals and adverse health effects. Residual oil fly ash (ROFA), a waste product of fossil fuel combustion from boilers, is rich in the transition metals Fe, Ni, and V, and when released as a fugitive particle, is an important contributor to ambient fine particulate air pollution. We hypothesized that a single-inhalation exposure to transition metal-rich PM will cause concentration-dependent cardiovascular toxicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
34
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 70 publications
7
34
1
1
Order By: Relevance
“…Importantly, our study identifies a charcoal and ash substrate as a new cue that signals antechinus to enhance torpor use to save energy. In rats and mice, exposure to particulate matter, such as ash, results in reduced heart rate or heart rate variability via vagal regulation and also causes lung inflammation (Swoap et al, 2008;Pham et al, 2009;Farraj et al, 2011). Additionally, as T b regulation involves the hypothalamus (Heller et al, 1977;Seebacher, 2009), a fast adjustment to the thermal physiology of the animal can be made, as the presence of these products of fire will herald a potential reduction in food availability.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, our study identifies a charcoal and ash substrate as a new cue that signals antechinus to enhance torpor use to save energy. In rats and mice, exposure to particulate matter, such as ash, results in reduced heart rate or heart rate variability via vagal regulation and also causes lung inflammation (Swoap et al, 2008;Pham et al, 2009;Farraj et al, 2011). Additionally, as T b regulation involves the hypothalamus (Heller et al, 1977;Seebacher, 2009), a fast adjustment to the thermal physiology of the animal can be made, as the presence of these products of fire will herald a potential reduction in food availability.…”
Section: Discussionmentioning
confidence: 99%
“…Animal models have shown that chronic exposure to air pollutants can produce significant changes in gene expression patterns (8,15,18,28,44), and in humans changes in transcriptional profiles have been correlated with air pollutant exposure (7,9,10,11,30,34,40,45). Together, these data show that pollutant-induced changes in gene expression levels have biological importance.…”
mentioning
confidence: 86%
“…miRNAs have been assessed in cell lines (125), human primary cell cultures (126)(127)(128), human peripheral blood leukocytes (129), tissues (122,130,131) and different body fluids (123,132,133). The latter surrogate samples have been widely used in oncology studies due to miRNA localization in microparticles and exosomes that confer high stability (123).…”
Section: Somatic Cell Mutationsmentioning
confidence: 99%
“…For instance, exposure to residual oil flay ash (ROFA), a fine particle product from oil combustion containing transition metals such as Ni, V and Fe, elicited cardiac dysfunction and altered miRNA expression levels in hypertensive rats (130). The study performed by Bollati, et al (2010), in peripheral blood leukocytes from a population of steel workers exposed to metal-rich particulate matter also identified overexpression of two miRNAs related to oxidative stress and inflammation regulation (miR-222 and miR-21) in exposed individuals.…”
Section: Somatic Cell Mutationsmentioning
confidence: 99%